O desenho instalado - o Lugar como origem e fim de um processo gráfico - Lírio, Regina Maria de Lamares Mendes Guedes da Piedade e (2006)
The structure of this dissertation sought to understand and place the scope of drawing within contemporary society, having as orientation lines: place as origin and end of a graphic process. The modus operandi sustained in the artistic activity itself for a specific place, the Corpus Christi Convent, structured the theoretical work, having as conceptual conjecture the process overtaking the finished work. This conjecture is further expanded and defended by Rene Passeron, from the poetics of the poem analyzed by Paul Valèry. The debate author-space-image has been articulated among the existent studies and the own considerations of the artists who have placed themselves in this field. Therefore, the theoretical and historical analysis of the concepts, sustained in the work of critics and artists who have manifested in this extended ground, has been extremely valuable for the perception of this artistic phenomenology. The expansion and delimitation of the field in Pierre Bourdieu and Rosalind Krauss, and the narrow course from the concept of site-specific to place-specific studied by Miwon Know as well as by Vaz-Pinheiro, alongside with the resonance of performance defended by Allan Krapow in Jackson Pollock s legacy, are some of the examples used to seek and fully understand the field of the installed drawing. Concepts as site, place, locus, context, memory, work and multiple subject, have generated a multiplicity of suggested diversified practices that indicate how contemporary art is simultaneously continuity and a rupture of the existent borders in the hybrid disciplinary fields. Finally, my artistic practice was thought and felt in the context of a place by installing drawings through acting means that, in a simultaneously individual and collective memory draw me back to my own memory of life.